Kemampuan Atraktan (Fermentasi Singkong dan Air Rendaman Udang Laut) pada Perangkap Nyamuk dalam Pengendalian Nyamuk - Yunicho Yunicho; Baharuddin Sunu; Tahniar Tahniar (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Muhammadiyah Makassar, 2020)
Mosquitoes are insects that act as vectors of disease. Some of the diseases caused by mosquitoes are Dengue Hemorrhagic Fever (DHF), filariasis, Malaria, Chikungunya and Encephalitis. Cases of mosquito-borne diseases are always increasing and can cause death. The purpose of this study was to determine the ability of attractant (fermented cassava and sea shrimp immersion) in mosquito traps in controlling mosquitoes. The research method used a quasi-experimental method. This research was conducted in Buhung Bundang Village, Bontotiro District, Bulukumba Regency. The results showed that the addition of attractants had the ability to attract mosquitoes to land on the traps. Of the two attractants used, fermented cassava was the most preferred attractant for mosquitoes compared to shrimp immersion attractant. The number of mosquitoes caught in all mosquito traps was 62. The number of mosquitoes in the cassava fermentation attractant was 36, while the shrimp immersion attractant was 26. The conclusion of this study shows that mosquito traps with the addition of attractants from fermented cassava and sea shrimp immersion can be used in mosquito control.